Practicality of Life Skills-based Student Worksheets to Improve Critical Thinking in Respiratory System Material of Senior High School - Lilis Setiawati; Sri Wulandari; Evi Suryawati (Journal of Educational Sciences, 2020)
This study aims to determine the practicality of life skill based student worksheets (LKPD) of class XI of high school on respiratory system material. The method used in the study was a research and development. The data source of this research was from two science teachers and thirty one students of class XI. The LKPD practicalities data was obtained through questionnaires practicalities of the device which was given to teachers and students.The analysis of the data used descriptive analysis that is to categorize the average score on learning process. Based on the analysis of the data, practicality of  LKPD through three assessment data, it showed that the first observation data with anaverage 97,4 % in a good category, the second dataquestionnaire responses of teachers with an average 95 % in a good category, and the third data questionnaire responses of students with an average 91% in a good category. Based on the analysis of the data, the practicality of the student worksheets has an average with the excellent category for all aspects. This shows that life skill based worksheet can be used as a biology learning medium in  high material school.